Preparation method of porous coated polyethylene proton exchange membrane
Through the preparation method of the porous coating polyethylene proton exchange membrane, the problem of low mechanical properties of the porous PTFE base film and poor compatibility of perfluorosulfonic acid resin in the prior art is solved, and a fuel cell membrane with high strength, ultra-thin, excellent proton conductivity and alcohol resistance performance is achieved, reducing cost and ohmic pressure drop.
Patent Information
- Application Number
- CN202411949543.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
In the existing proton exchange membrane fuel cells, the mechanical properties of the porous PTFE base film are not high, and the perfluorosulfonic acid resin has poor compatibility with the base film, which affects the conductivity and gas permeability, resulting in high cost and low efficiency of the fuel cell.
The preparation method of porous coating polyethylene proton exchange membrane is adopted, and the mechanical properties of the base film and the compatibility of perfluorosulfonic acid resin are improved through surface treatment and casting technology, forming a dense internal structure and reducing fuel crossing.
The high strength and ultra-thin thickness of the porous coating polyethylene proton exchange membrane are achieved, the mechanical strength reaches more than 150MPa, and the proton conductivity and alcohol resistance performance have also been significantly improved, reducing the cost and ohmic pressure drop of the fuel cell.
Smart Images

Figure CN119764501A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of proton exchange membrane fuel cells, in particular to a method for preparing a porous coated polyethylene proton exchange membrane. Background Art
[0002] Hydrogen fuel cells have the outstanding advantages of extremely high energy conversion efficiency, extremely high energy density and zero pollution. Among them, proton exchange membrane fuel cells are most widely used in the field of electric vehicles. The proton exchange membrane is its key component, which involves the power output, life and cost of the fuel cell. Therefore, the ideal proton exchange membrane needs to have high proton conductivity, low gas permeability, high mechanical properties, excellent chemical stability and low cost.
[0003] What the proton exchange membrane fuel cell mainly adopts at present is perfluorosulfonic acid type proton exchange membrane, such as Nafion series membrane of DuPont, USA, this kind of membrane has good proton conduction ability and chemical stability, but its processing technology is relatively complicated and expensive. More importantly, because its inherent strength is not very high, pure perfluorosulfonic acid type proton exchange membrane must have a certain thickness, and its strength can meet the actual needs of fuel cell (it is generally believed that the dry thickness should be more than 50um), such thickness causes the cost of fuel cell in membrane aspect to be higher, and because the ohmic pressure drop is almost linearly related to the thickness of membrane in the battery operation, the ohmic pressure drop caused by the thickness of membrane is very large [Journal of Membrane Science237, 2004, 1-7, US Patent 5,547,551].
[0004] However, the composite reinforced membrane faces the problem of compatibility between perfluorosulfonic acid resin and the base membrane, which affects the conductivity and gas permeability of the membrane; the most commonly used porous PTFE base membrane has low mechanical properties, and the mechanical properties of the prepared composite membrane are general (<30MPa); and the wider proton transmission channels of the porous PTFE base membrane also lead to a higher methanol permeability, reducing battery efficiency. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a porous coated polyethylene proton exchange membrane.
[0007] (II) Technical solution
[0008] Based on this, the present invention provides the following technical solution: a method for preparing a porous coated polyethylene proton exchange membrane, wherein the specific preparation steps are as follows:
[0009] Step S1: surface treatment: treating the surface of the porous coated polyethylene film to obtain an activated substrate film, wherein the surface treatment method comprises ultraviolet radiation treatment, plasma treatment, active solvent treatment and surface oxidation treatment; wherein, the ultraviolet radiation treatment has a wavelength range of 80-280nm; the plasma treatment has a pressure of 5-10KPa, and the plasma gas is one of N2, O2, NH3, CO2, Ar, He and H2O; the active solvent treatment has a solvent of one or more of methanol, ethanol, tetrahydrofuran, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide; the surface oxidation treatment has an oxidation solution in which the solvent is water and the solute is one or more of potassium dichromate, potassium permanganate, nitric acid, nitrous acid, hypochlorous acid and hydrogen peroxide;
[0010] Step S2: Preparation of perfluorosulfonic acid resin solution: First, dissolve the perfluorosulfonic acid resin in a polar solvent, stir at 60° C. until completely dissolved, and prepare a resin solution with a mass concentration of 20wt%; secondly, place it in a vacuum degassing machine for 1.5 hours to remove bubbles in the resin solution, and the polar solvent is one or more of tetrahydrofuran, acetonitrile, methanol, ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide;
[0011] Step S3: tape casting: pour the resin solution into the solution tank of the tape casting machine, so that the surface-treated porous coated polyethylene film passes through the solution tank to obtain an impregnated membrane in which the base membrane is impregnated with the resin solution; the impregnated membrane passes through a scraper with a height range of 150-500μm, enters a normal pressure oven, and is dried at a temperature of 65-95°C for 1.2-5h to obtain a porous coated polyethylene proton exchange membrane with a thickness of 3.6-20μm.
[0012] Preferably, the preparation steps of the porous coated polyethylene film are as follows:
[0013] Step Q1: Dissolve 2 g of PVA in a beaker containing 30 mL of distilled water and heat until it is completely dissolved;
[0014] Step Q2: Then put the beaker into an ice water bath, keep the temperature at 0-4°C, slowly add excess concentrated sulfuric acid while stirring. Put the beaker into a 40°C water bath, heat and stir for 3h;
[0015] Step Q3: Anhydrous ethanol is poured into the reaction mixture, and a white precipitate is precipitated. The mixture is continuously rinsed with anhydrous ethanol until the pH value of the mixture reaches 6.0. The generated SPVA is then placed in an oven and dried at 50° C. for 24 h.
[0016] Step Q4: The side chain sulfonated polyaryletherketone and SPVA are then dissolved in dimethyl sulfoxide (DMSO) respectively, and then the two polymer solutions are mixed, stirred evenly, spread on a glass plate, placed in an oven, and dried at 60°C for 24 hours to prepare a porous coated polyethylene proton exchange membrane.
[0017] Preferably, the mass fraction of the SPVA is 5%-30%, and the average thickness of the porous coated polyethylene proton exchange membrane is about 60-80 μm.
[0018] (III) Beneficial effects
[0019] Compared with the prior art, the present invention provides a method for preparing a porous coated polyethylene proton exchange membrane, which has the following beneficial effects:
[0020] The porous coated polyethylene proton exchange membrane preparation method has better compatibility with perfluorosulfonic acid resin, and suitable surface treatment is used to enhance the hydrophilicity of the base membrane, so that the prepared composite proton exchange membrane forms a dense internal structure, which can effectively prevent fuel crossover; since the porous coated polyethylene proton exchange membrane has the characteristics of moderate crystallization, it has high strength and ultra-thin thickness, and the prepared composite membrane inherits these two points well, and the thickness can reach an ultra-thin minimum of 4μm, and the mechanical strength reaches an ultra-strong mechanical strength of more than 150MPa; and with the introduction of SPVA in the porous coated polyethylene proton exchange membrane, the water absorption rate and water retention capacity of the composite membrane are improved, thereby improving the proton conductivity of the composite membrane, and within a certain SPVA content, it increases with the increase of SPVA content, and the alcohol resistance of the membrane is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the SPVA synthesis route of the present invention. DETAILED DESCRIPTION
[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] See also Figure 1, a method for preparing a porous coated polyethylene proton exchange membrane, the specific preparation steps are as follows: Step S1: surface treatment: treating the surface of the porous coated polyethylene film to obtain an activated base film, the surface treatment method includes ultraviolet radiation treatment, plasma treatment, active solvent treatment and surface oxidation treatment; wherein, the ultraviolet radiation treatment has a wavelength range of 80-280nm; the plasma treatment has a pressure of 5-10KPa, and the plasma gas is one of N2, O2, NH3, CO2, Ar, He and H2O; the active solvent treatment has a solvent of one or more of methanol, ethanol, tetrahydrofuran, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; the surface oxidation treatment has an oxidation solution in which the solvent is water and the solute is one or more of potassium dichromate, potassium permanganate, nitric acid, nitrous acid, hypochlorous acid and hydrogen peroxide;
[0024] Step S2: Preparation of perfluorosulfonic acid resin solution: First, dissolve the perfluorosulfonic acid resin in a polar solvent, stir at 60° C. until completely dissolved, and prepare a resin solution with a mass concentration of 20wt%; secondly, place it in a vacuum degassing machine for 1.5 hours to remove bubbles in the resin solution, and the polar solvent is one or more of tetrahydrofuran, acetonitrile, methanol, ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide;
[0025] Step S3: tape casting: pour the resin solution into the solution tank of the tape casting machine, so that the surface-treated porous coated polyethylene film passes through the solution tank to obtain an impregnated membrane in which the base membrane is impregnated with the resin solution; the impregnated membrane passes through a scraper with a height range of 150-500μm, enters a normal pressure oven, and is dried at a temperature of 65-95°C for 1.2-5h to obtain a porous coated polyethylene proton exchange membrane with a thickness of 3.6-20μm.
[0026] The preparation steps of the porous coated polyethylene film are as follows:
[0027] Step Q1: Dissolve 2 g of PVA in a beaker containing 30 mL of distilled water and heat until it is completely dissolved;
[0028] Step Q2: Then put the beaker into an ice water bath, keep the temperature at 0-4. C, slowly add excess concentrated sulfuric acid while stirring. Put the beaker into a 40°C water bath, heat and stir for 3 hours. The reaction process is as follows: Figure 1 As shown;
[0029] Step Q3: Anhydrous ethanol is poured into the reaction mixture, and a white precipitate is precipitated. The mixture is continuously rinsed with anhydrous ethanol until the pH value of the mixture reaches 6.0. The generated SPVA is then placed in an oven and dried at 50° C. for 24 h.
[0030] Step Q4: The side chain sulfonated polyaryletherketone and SPVA are then dissolved in dimethyl sulfoxide (DMSO) respectively, and then the two polymer solutions are mixed, stirred evenly, spread on a glass plate, placed in an oven, and dried at 60°C for 24 hours to prepare a porous coated polyethylene proton exchange membrane.
[0031] The mass fraction content of SPVA is 5%-30%, and the average thickness of the porous coated polyethylene proton exchange membrane is about 60-80 μm, specifically: 5%, 10%, 15%, 20%, 25%, 30%, respectively marked as S-SPAE / SPVA5, S-SPAE / SPVA10, S-SPAE / SPVA15, S-SPAE / SPVA20, S-SPAE / SPVA25, S-SPAE / SPVA30.
[0032] Proton conductivity of porous coated polyethylene proton exchange membrane
[0033] As can be seen from Table 1, due to the introduction of SPVA, the proton conductivity of the porous coated polyethylene proton exchange membrane increased, and increased with the increase of SPVA content (the pH value test confirmed that the sulfate bond on the SPVA in the composite membrane did not undergo hydrolysis reaction, which would not affect the test result of proton conductivity). Due to the introduction of SPVA, the water absorption rate of the composite membrane increased, which was beneficial to the transfer of protons according to the "Vehicle" mechanism and the "Grotthuss" mechanism, thereby improving the proton conductivity: On the other hand, due to the introduction of hydrophilic sulfonic acid groups in SPVA, the number of hydrophilic groups in the membrane increased. According to the proton transfer mechanism, the proton conductivity of the membrane at low humidity will decrease. As can be seen from Table 1, this series of composite membranes has a higher proton conductivity at 80°C, and since the water retention capacity of the membrane increases with the increase of SPVA content, the proton conductivity of the membrane at 80°C also increases accordingly.
[0034] Table 1 Analysis data of S-SPAEK and S-SPAEK / SPVA composite membranes
[0035]
[0036] Methanol permeability of porous coated polyethylene proton exchange membrane
[0037] As can be seen from Table 1, the methanol permeability coefficient of the composite membrane decreases significantly with the increase of SPVA content. PVA preferentially permeates water, but has a blocking effect on alcohol, and the higher the alcohol concentration, the greater the separation coefficient. Although SPVA is partially sulfonated, it still has alcohol barrier properties. This is because methanol is a poor solvent for SPVA. When the methanol concentration is very high, the hydrophilic SPVA molecular chain will curl and shrink, which will lead to a decrease in the free volume between the polymer molecular chains. Since the size of water molecules is smaller than that of methanol molecules, when PEM shrinks, it is beneficial to improve the diffusion selectivity of the membrane to water and reduce the permeability of the membrane to methanol. At the same time, since SPVA has a poor solvent for water, Very high affinity, so when the methanol concentration is very high, the water concentration in the membrane is much greater than the water concentration in the fuel liquid, thereby improving the membrane's solubility selectivity for water. It is precisely because of these two aspects that SPVA has a good separation effect on solutions with high methanol concentrations. SPVA is easy to gather in the hydrophilic phase area of the membrane. During the proton conduction process, protons and water combine to form hydrated protons. SPVA prefers to diffuse water, and hydrated protons can preferentially pass through these transmission channels of the membrane, while the transmission of methanol molecules is hindered. It can be said that the membrane preferentially conducts protons and has a hindering effect on alcohol. Therefore, the introduction of SPVA improves the alcohol barrier performance of the porous coated polyethylene proton exchange membrane.
[0038] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a porous coated polyethylene proton exchange membrane, characterized in that: The specific preparation steps are as follows: Step S1: Surface treatment: treating the surface of the porous coated polyethylene film to obtain an activated base film; Step S2: Preparation of perfluorosulfonic acid resin solution: First, dissolve the perfluorosulfonic acid resin in a polar solution, stir at 60°C until completely dissolved, and prepare a resin solution with a mass concentration of 20wt%; second, place it in a vacuum degassing machine for 1.5h to remove bubbles in the resin solution; Step S3: tape casting: pouring the resin solution into the solution tank of the tape casting machine, so that the surface-treated porous coated polyethylene film passes through the solution tank to obtain an impregnated film in which the base film is impregnated with the resin solution; The impregnated membrane passes through a scraper with a height range of 150-500 μm, enters a normal pressure oven, and is dried at a temperature of 65-95° C. for 1.2-5 hours to obtain a porous coated polyethylene proton exchange membrane with a thickness of 3.6-20 μm.
2. The method for preparing a porous coated polyethylene proton exchange membrane according to claim 1, characterized in that: The preparation steps of the porous coated polyethylene film are as follows: Step Q1: Dissolve 2 g of PVA in a beaker containing 30 mL of distilled water and heat until it is completely dissolved; Step Q2: Then put the beaker into an ice water bath, keep the temperature at 0-4°C, slowly add excess concentrated sulfuric acid while stirring. Put the beaker into a 40°C water bath, heat and stir for 3h; Step Q3: Anhydrous ethanol is poured into the reaction mixture, and a white precipitate is precipitated. The mixture is continuously rinsed with anhydrous ethanol until the pH value of the mixture reaches 6.
0. The generated SPVA is then placed in an oven and dried at 50° C. for 24 h. Step Q4: The side chain sulfonated polyaryletherketone and SPVA are then dissolved in dimethyl sulfoxide (DMSO) respectively, and then the two polymer solutions are mixed, stirred evenly, spread on a glass plate, placed in an oven, and dried at 60°C for 24 hours to prepare a porous coated polyethylene proton exchange membrane.
3. The method for preparing a porous coated polyethylene proton exchange membrane according to claim 2, characterized in that: The mass fraction content of the SPVA is 5%-30%, and the average thickness of the porous coating polyethylene proton exchange membrane is about 60-80 μm.
4. The method for preparing a porous coated polyethylene proton exchange membrane according to claim 1, characterized in that: As in step S1 above, the surface treatment method includes ultraviolet radiation treatment, plasma treatment, active solvent treatment and surface oxidation treatment; wherein the ultraviolet radiation treatment has a wavelength range of 80-280nm; the plasma treatment has a pressure of 5-10KPa, and the plasma gas is one of N2, O2, NH3, CO2, Ar, He and H2O; In the active solvent treatment, the solvent is one or more of methanol, ethanol, tetrahydrofuran, acetonitrile, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide; in the surface oxidation treatment, the solvent in the oxidation solution is water, and the solute is one or more of potassium dichromate, potassium permanganate, nitric acid, nitrous acid, hypochlorous acid, and hydrogen peroxide.
5. The method for preparing a porous coated polyethylene proton exchange membrane according to claim 1, characterized in that: As in step S2 above, the polar solvent is one or more of tetrahydrofuran, acetonitrile, methanol, ethanol, N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, and dimethyl sulfoxide.
Citation Information
Patent Citations
Ultra-thin integral composite membrane
US5547551A